Efektivitas Pemberian Edukasi Tentang Kebersihan Gigi dan Mulut Terhadap Penurunan Kejadian Karies Gigi Pada Anak Usia Sekolah di MI Muwaffaq Islamic School - Imroatulhuda Wijaya; Vivi Melisa Barus (Politeknik Ganesha Medan, 2025)
Dental caries is one of the most common oral health problems among school-aged children and can adversely affect their growth and quality of life. A lack of knowledge regarding oral hygiene practices is one of the main contributing factors to the high prevalence of dental caries. This study aims to determine the effectiveness of oral health education in reducing the incidence of dental caries among school-aged children. This research employed a pre-experimental design using a one-group pre-test and post-test approach. The sample consisted of 148 students from MI Muwaffaq Islamic School, selected through stratified random sampling. Data were collected using questionnaires and ICDAS observation sheets and analyzed using the Wilcoxon test. The results indicated a significant improvement in children’s knowledge after receiving oral health education, with the proportion of students demonstrating good knowledge increasing from 55.4% to 86.5%. The Wilcoxon test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between pre- and post-intervention scores. Additionally, 53.4% of the children did not experience dental caries following the educational intervention. In conclusion, oral health education is effective in enhancing children’s knowledge of dental hygiene and reducing the incidence of dental caries.